Nutrient-dense orange-fleshed sweetpotato: advances in drought-tolerance breeding and understanding of management practices for sustainable next-generation cropping systems in Sub-Saharan Africa - Low, Jan W.; Ortíz, R.; Vandamme, Elke; Andrade, M.I.; Temesgen, B.B.; Grüneberg, W.J. (Frontiers Media, 2020)
Almost half of children <5 years old living in sub-Saharan Africa (SSA) suffer from vitamin A deficiency and 60% suffer from iron deficiency. Thus, there has been a strong commitment to breeding for, promoting awareness of, and delivering adapted pro-vitamin A rich orange-fleshed sweetpotato (OFSP) in SSA during the past two decades and for enhanced iron content since 2014. This review article focuses on major breeding efforts in SSA to enhance the drought tolerance of OFSP and reviews integrated crop management practices for improved and sustained sweetpotato production in SSA farming systems. Under climate change, the frequency and severity of droughts is expected to increase. Technical issues are presented in the context of addressing challenges along the entire value chain to ensure adoption. First, the use of an accelerated breeding scheme reduced the breeding cycle from 8–10 to 4–5 years. Since 2010, 19 drought-tolerant OFSP cultivars have been released in Mozambique, 7 in Malawi, and 2 in South Africa. Moreover, research in four breeding populations using the heterosis exploiting breeding scheme (HEBS) demonstrated that within one breeding cycle of 5 years, clones with significantly higher root yield, abiotic tolerance, host plant resistance to pests and diseases, and early maturity can be produced. In the future, HEBS will be combined with greater use of modern genomic tools, new phenotyping tools, and CRISPR/Cas9-mediated gene editing. Second, beyond genetic enhancements, evidence is presented that using improved crop management systems, existing sweetpotato yields can be increased 2–4 times. Current knowledge is reviewed concerning sweetpotato's role in diverse farming systems, but integrated crop management is clearly under researched. Third, the outlook for drought tolerance breeding indicates that two distinct classes of nutrient-rich cultivars are emerging: (1) Early maturing cultivars (<4 month growing period) that escape drought but also serve humid environments with small landholding size per capita; and (2) Medium maturing (4–6 month growing period) cultivars that avoid drought, are drought tolerant and exhibit continuous root formation. Increasing commercialization of the crop and climate change will drive demand, and the willingness of farmers to invest in improved sweetpotato crop management.